Effects of cold water immersion after exercise on fatigue recovery and exercise performance--meta analysis - Xiao, F.; Kabachkova, A. V.; Jiao, L.; Zhao, H.; Kapilevich, L. V. (Frontiers in Physiology, 2023)
Cold water immersion (CWI) is very popular as a method reducing post-exercise muscle stiffness, eliminating fatigue, decreasing exercise-induced muscle damage (EIMD), and recovering sports performance. However, there are conflicting opinions as to whether CWI functions positively or negatively. The mechanisms of CWI are still not clear. In this systematic review, we used meta-analysis aims to examine the effect of CWI on fatigue recovery after high-intensity exercise and exercise performance. A total of 20 studies were retrieved and included from PubMed, PEDro and Elsevier databases in this review. Publication years of articles ranged from 2002 to 2022. In selected studies including randomized controlled trials (RCTs) and Crossover design (COD). Analyses of subjective indicators such as delayed-onset muscle soreness (DOMS) and ratings of perceived exertion (RPE), and objective indicators such as countermovement jump (CMJ) and blood plasma markers including creatine kinase(CK), lactate/lactate dehydrogenase(LDH), C-reactive protein(CRP), and IL-6 were performed. Pooled data showed as follows: CWI resulted in a significant decline in subjective characteristics (delayed-onset muscle soreness and perceived exertion at 0 h); CWI reduced countermovement jump(CMJ) significantly at 0 h, creatine kinase(CK) was lowered at 24 h, and lactate at 24 and 48 h. There was no evidence that CWI affects C-reactive protein(CRP) and IL-6 during a 48-h recovery period. Subgroup analysis revealed that different CWI sites and water temperatures have no effect on post-exercise fatigue recovery. Recommended athletes immersed in cold water immediately after exercise, which can effectively reduce muscle soreness and accelerate fatigue recovery.